Foundation phase teachers' understanding and implementation of differentiated pedagogical practices in teaching reading - Muroa, Johanna Makgati (Rhodes University, Faculty of Education, Department of Primary and Early Childhood Education)
Pre-1994, teacher education in South Africa was separated into mainstream and special education classes. Special education classes accommodated learners who were not coping with grade-level work. In 2001, Education White Paper Six advocated for inclusive education. This policy promotes differentiated pedagogical practices to accommodate learners' needs and minimize barriers to learning. However, research has shown that teachers do not have the required content and pedagogical knowledge to teach according to diverse learners' needs. One of the reasons given is that the teacher education system does not prepare teachers adequately to teach in classrooms with diverse learners. This qualitative case study is underpinned by an interpretivist orientation as it seeks to ascertain how teachers understand and implement differentiated pedagogical tools in their practice. The research asks the question: How do Foundation Phase teachers understand and implement differentiated pedagogical tools? Seventy-six teachers enrolled for in-service Bachelor of Education (Foundation Phase) completed a questionnaire and three Foundation Phase teachers were observed and interviewed. Data gathered was analyzed using the Theory of Practice Architectures. The study found that the teachers recognized the importance of accommodating the different learners' learning needs, however, they struggled to implement differentiated pedagogical practices in the classroom.
Keywords: Teachers Training of; Differentiated teaching staffs; Reading comprehension -- Study and teaching (Elementary); Reading; Appropriation